Penentuan Tarip Jasa Rawat Inap RSUD “Dr.H.Soewondo” Kendal (Studi Kasus) - Susatyo Herlambang (EBBANK, 2014)
RSUD "Dr.H.Soewondo" Kendal represent the government hospital and its orientation service to society, while defrayal of hospital management also taken away from a service rate, hence determination of service rate also adapted by a condition and also existing society circumstance, from the circumstance hence needed calculation of expense and elegibility to rate. The rate have according to high or not  against the society?